SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KOPERASI TERBAIK DINAS PERDAGANGAN PERINDUSTRIAN DAN KOPERASI MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI KOTA SERANG - Ahmad Surahmat; Tubagus Dedy Fuady (LPPM Unbaja, 2022)
A cooperative is a business entity consisting of a person or a cooperative legal entity by basing its activities on the cooperative principle as well as the people's economic movement based on the principles of kinship. The Department of Industry, Trade and Cooperatives has the main task and function of fostering and progressing, DISPERDAGINKOP also provides an assessment which will later select the best cooperative and then get an award at the cooperative anniversary event. So far, the DISPERDAGINKOP of Serang City has assessed that each existing cooperative has not been effective and time-consuming. Because there are quite a lot of cooperatives that must be assessed in Serang City. The assessment data from each cooperative that is judged to be in accordance with the criteria with a manual assessment process referred to manually is input data in the form of a cooperative assessment form that has been given an assessment of the existing criteria and then processed using Microsoft Excel. To solve existing problems, an application was made to make it easier to manage the assessment results of each cooperative. In decision-making, it is necessary to have accurate data for the assessment process so that there are no errors in the decision-making process. In this study using the AHP (Analytical Hierarchy Process) method where in the assessment there are predetermined criteria, in terms of assessing the existence of alternatives that will be assessed and compared with one another from each of the existing criteria, then produce the final value of each cooperative, as well as increasing the effectiveness of the decision-making process, with the aim of obtaining data more quickly and accurately and increasing time efficiency.